Effect of Rearing Season on Meat and Intramuscular Fat Quality of Beni-Guil Sheep - Kamal Belhaj; Farid Mansouri; Marianne Sindic; Marie-Laure Fauconnier; Mohamed Boukharta; Hana Serghini Caid; Ahmed Elamrani (Journal of Food Quality)
Twenty Beni-Guil-PGI female lambs were used to study the effects of rearing season on meat quality characteristics, fatty acids profile, and lipid content. The animals were reared according to the pastoral-transhumant system in the eastern region of Morocco. The treatments consisted of 10 female lambs reared in summer-autumn (SA) and slaughtered at winter season and 10 female lambs reared in winter-spring (WS) and slaughtered at spring season. After the slaughter, the longissimus lumborum was collected for each animal for meat quality analysis. Compared to lambs reared in SA, the meat from the WS group showed higher (p<0.01) pH, chroma, and lightness values (5.79 vs. 5.72, 23.97 vs. 18.46, and 47.03 vs. 41.04, respectively). On the other hand, the meat from WS presented higher (p<0.05) intramuscular fat content (5.14 % vs. 3.82%, respectively). However, the intramuscular fat of the lambs reared in SA was characterized by greater (p<0.01) PUFA percentage (16.82% vs. 12.40%, respectively), thrombogenic (p<0.001) and atherogenic index (p<0.001), and PUFA/SFA ratio (p<0.01; 0.42 vs. 0.25, respectively). Nevertheless, those reared in WS season have a higher (p<0.001) PUFA n − 3 (2.58% vs. 1.14%, respectively) content, and therefore favorable (p<0.001) n − 6/n − 3 ratio (3.78 vs. 12.98, respectively).